2003
DOI: 10.1161/01.cir.0000089183.92233.75
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Aortic Root Late After Ross Operation

Abstract: Background-The Ross operation is an alternative to mechanical aortic valve replacement in the young. Early dilatation of the pulmonary autograft root exposed to the systemic circulation has been reported. To define the prevalence of, risk factors for, and consequences of late autograft dilatation, outcome in all consecutive patients operated since May 1994 was reviewed. Methods and Results-Ninety one patients, 77 males and 14 females, with at least 1 year of follow-up underwent cross-sectional clinical and ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 30 publications
5
106
0
Order By: Relevance
“…In one series of 91 patients, the incidence of pulmonary autograft root dilatation was 61% at 5 years among those with a prior aortic aneurysm, compared with 27% among those with no prior aortic aneurysm (ie, those who had surgery for aortic valve disease only). 24 When full aortic root/valve replacement is necessary, another alternative to a composite graft is the use of cryopreserved aortic allografts (cadaveric aortic root and proximal ascending aorta). However, after the procedure, late structural valvular deterioration does occur and may lead to subsequent reoperation.…”
Section: Ascending Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…In one series of 91 patients, the incidence of pulmonary autograft root dilatation was 61% at 5 years among those with a prior aortic aneurysm, compared with 27% among those with no prior aortic aneurysm (ie, those who had surgery for aortic valve disease only). 24 When full aortic root/valve replacement is necessary, another alternative to a composite graft is the use of cryopreserved aortic allografts (cadaveric aortic root and proximal ascending aorta). However, after the procedure, late structural valvular deterioration does occur and may lead to subsequent reoperation.…”
Section: Ascending Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…32 Other authors have reported progressive dilation of the autograft with differential prevalence, depending on the definition used (generally 4.0 cm or greater), the method used for detection, and the duration of follow-up. 11 Predisposing factors favoring dilation have included anatomic mismatch between the pulmonary and aortic root and a complete aortic root replacement technique without pericardial buttressing of the ascending aorta and annulus. 11,31,33 …”
Section: Mortalitymentioning
confidence: 99%
“…The Ross operation (use of the pulmonary valve as an autograft) introduced in 1967 10 has emerged as an attractive alternative, but concerns persist about the fate of the neoaortic valve, the potential for development of neoaortic valve insufficiency, and the lack of consistent long-term outcome data. [11][12][13][14] In addition, autograft use often necessitates repeated interventions for right ventricular outflow tract obstruction. 3,12 In addition to prosthesis failure and reoperation, children are simultaneously at an increased risk of death after AVR.…”
mentioning
confidence: 99%
“…However, recent studies show that reoperation requirement in 10 years is 25% in autografts and 14% in allografts (25). This complication is more common in patients who are young and in patients with aortic dilatation before the surgery (26). To prevent posterior dilatation in patients who underwent Ross procedure, using inclusion techniques, homograft and allograft wraps are suggested.…”
Section: The Repairment Of the Aortic Valvementioning
confidence: 99%